The impact of lead users on innovation success: The mediating impact of knowledge sharing case of IT companies - Reem Marzouki; Wafa Belkahla (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to study the impact of lead users (LUs) on innovation success by proposing and validating an integrative model that links LUs, innovation success and knowledge sharing (KS) variables. Design/methodology/approach - The authors research is quantitative in nature and data were collected through a survey conducted among 30 information technology Tunisian companies. The authors preliminary analysis was explored using the "SPSS" software and processed through exploratory factor analysis and regression analysis methods. Findings - Results showed that LUs who possess advanced skills and valuable knowledge can contribute to enhance new successful innovations, and hence, enable companies to gain short and long-term profits. Besides, the authors confirmed that the impact of LUs on innovation success is mediated by the "KS" behavior. Practical implications - An integrative framework that links LUs, innovation success and a third variable called KS is presented to see beyond the intended importance of this type of user regarding the development of new innovations. Originality/value - The paper offers new insights to the topic of LUs by emphasizing the role of "KS" variable in strengthening the LUs - innovation success relationship.
Keywords: 650; Knowledge sharing; Lead users; Innovation success; IT companies